(untitled) (LACCEI, 2024)
The influence of the retention time and proportion of Zea mays corn cob in the acid mine drainage for the total removal of iron and lead from the Hualgayoc-Arascorgue river was studied, focusing on the effectiveness of bioadsorption using Zea Mays corn cob as an adsorbent material for removing iron and lead from the residual water of the Hualgayoc-Arascorgue river. The research was of an explanatory-experimental and quantitative nature, using 30 liters of residual water and 1,350 kg of Zea mays corn cob as a sample. The results indicated that the retention time did not have a significant influence on lead removal, but there was an influence on iron removal in relation to the proportion of Zea mays corn cob used. It is recommended to conduct a kinetics study of adsorption before any research related to metal bioadsorption, and to promote the implementation of clean technologies for environmental conservation.